Optimalisasi Konsentrasi Pepton Ikan Pada Media Kultur terhadap Pertumbuhan Probiotik Lactiplantibacillus plantarum Kita-3 - Dewi, Made Ayu Shintya; Nocianitri, Komang Ayu; Hatiningsih, Sayi; Rahayu, Endang Sutriswati (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i03.p14, 2024)
Culture media are essential for providing nutrients that support the growth of probiotic bacteria. Reducing the concentration of substrates like peptone can lower production costs, but it may also slow down the growth of the probiotic bacteria. This study aims to optimize the concentration of fish peptone as a nitrogen source in culture media and determine the most efficient concentration for supporting the growth of the probiotic L. plantarum Kita-3. A Completely Randomized Design (CRD) was employed, with peptone concentrations (12,5%, 18,75%, 25%) as treatment factors. Each treatment was repeated twice, resulting in six experimental units. Descriptive analysis was used for data examination, while total LAB was analyzed using the non-parametric Kruskal-Wallis statistical method. The Mann-Whitney test was conducted if significant effects (P<0.05) were detected among treatments. Results indicated that the peptone concentration from fish did not significantly affect (P>0.05) the growth of L. plantarum Kita-3. The optimal concentration of fish peptone for supporting the growth of L. plantarum Kita-3 was determined to be 12,5%, with a final incubation pH of 3,87, final total LAB of 9,05 log cfu/ml, probiotic powder weight of 5,20 gr, and total LAB in the probiotic powder reaching 11,28 log cfu/gr. Keywords: probiotic powder, fish, peptone concentration from fish, Lactiplantibacillus plantarum Kita-3